PENGARUH PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN (Perusahaan Property Dan Real Estate Yang Terdaftar Di Bursa Efek Indonesia) - Erni Safitri, 13.05.52.0117; Srimindari, Ceacilia (Students Journal of Accounting and Banking, 2017)
One of the long-term goals to be achieved by the company is increasing the value of the companys high. There are several factors that can affect the value of the company, including the companys profitability and size. The purpose of this study to determine the effect that proxy Profitability (Return On Assets) and the size of the company in the value of the company. The population is all company property and real estate in the Indonesia Stock Exchange in 2012-2015. The sampling technique used was purposive sampling. The analytical tool used in this research is multiple regression analysis and regression analysis moderation. The results of this study found that the size of the companys profitability variable and significant positive effect on firm value.Keywords:Â Profitability (ROA), Company Size, and Corporate Values (Tobins Q)